Ab initio nanofluidics: disentangling the role of the energy landscape and of density correlations on liquid/solid friction. Issue 20 (19th May 2020) - Tocci, Gabriele; Bilichenko, Maria; Joly, Laurent; Iannuzzi, Marcella
Abstract : Ab initio molecular dynamics reveals that subtle variations in the energy landscape and density correlations can change by up to one order of magnitude the slippage of water on two-dimensional materials. Abstract : Despite relevance to water purification and renewable energy conversion membranes, the molecular mechanisms underlying water slip are poorly understood. We disentangle the static and dynamical origin of water slippage on graphene, hBN and MoS2 by means of large-scale ab initio molecular dynamics. Accounting for the role of the electronic structure of the interface is essential to determine that water slips five and eleven times faster on graphene compared to hBN and to MoS2, respectively. Intricate changes in the water energy landscape as well as in the density correlations of the fluid provide, respectively, the main static and dynamical origin of water slippage. Surprisingly, the timescales of the density correlations are the same on graphene and hBN, whereas they are longer on MoS2 and yield a 100% slowdown in the flow of water on this material. Our results pave the way for an in silico first principles design of materials with enhanced water slip, through the modification of properties connected not only to the structure, but also to the dynamics of the interface.